1999
DOI: 10.1539/joh.41.177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electromagnetic Field on Serum Biochemical Parameters in Steelworkers

Abstract: Effect of Electromagnetic Field on Serum Biochemical Parameters in Steelworkers: Boguslaw KULA, et al. Department of Biochemistry and Chemistry, Medical University of Silesia—The aim of the study was to evaluate some biochemical parameters in the serum of steelworkers exposed to electromagnetic field (electric field strength of 20 V/m and magnetic field strength of 2 A/m) generated by induction heaters. We found significant decreases in the levels of total protein, β-and γ-globul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 8 publications
4
24
2
Order By: Relevance
“…In addition, the adverse effects of artificial electromagnetic fields on the red bone marrow and the erythrocyte production on the liver of workers who were exposed to them. The evident decrease in the level of protein and globulin might be a sign of the chronic inflammation process [23]. Jimenez Garcia et al (2010) showed that the exposure of rats to rays with a frequency of 120 Hz and an intensity of 4.5 milli-Tesla reduces cell proliferation and thus prevents the destruction of the induced neoplastic by the chemical agents in the rat's liver.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the adverse effects of artificial electromagnetic fields on the red bone marrow and the erythrocyte production on the liver of workers who were exposed to them. The evident decrease in the level of protein and globulin might be a sign of the chronic inflammation process [23]. Jimenez Garcia et al (2010) showed that the exposure of rats to rays with a frequency of 120 Hz and an intensity of 4.5 milli-Tesla reduces cell proliferation and thus prevents the destruction of the induced neoplastic by the chemical agents in the rat's liver.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found in rats (Bellossi, et al, 1998) and mice (Kumosani and Qari , 2003) as well as in human. The most pronounced change was found in steelworker deal with large exposure to EMF (Kula et al, 1999). The mechanisms of the effect of EMF (which affect water quality) after exposure to magnetic funnel on lipid metabolism have not been well understand yet.…”
Section: Blood Lipids Profilementioning
confidence: 99%
“…ELF-MF affects cell membranes by changing ions transports and membrane maintaining [10]. It can affect magnetically increase free radical production by chemical process at the atomic levels [11].…”
Section: Introductionmentioning
confidence: 99%